Preparation method and application of large-size high-strength electronic glass

By adopting multi-component glass materials and specific process flows, the existing silicate glass has low yield, many defects and low strength in large-scale, high-strength, and high-transmissive ultra-thin electronic glass applications, and large-size electronic glass with high-strength and high transmittance suitable for large-scale photoelectric display equipment has been prepared.

CN119528419APending Publication Date: 2025-02-28CLFG LONGHAI ELECTRONICS GLASS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411813126.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the applications of large-size, high-strength, high-transmission ultra-thin electronic glass, existing silicate glass has problems such as low yield, many defects and low strength, which is difficult to meet the needs of large-scale photoelectric display equipment.

Method used

Using multi-component glass materials, including SiO2, Na2O, CaO, Al2O3, MgO, K2O, TiO2, ZrO2 and B2O3, large-size high-strength electronic glass is prepared through specific smelting and molding processes. The process includes smelting, float forming, annealing, grinding and reheat treatment to ensure high transmittance, strength and stability of the glass.

Benefits of technology

The large-size high-strength electronic glass prepared has good bending strength, transparency and hardness, and is suitable for display layers and back covers of large-scale photoelectric display equipment, meeting the needs of high strength, high transmittance and large size.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528419A_ABST
    Figure CN119528419A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of large-size high-strength electronic glass, and relates to the technical field of photoelectric display glass, matrix glass prepared through the method has high transmittance, the surface of the matrix glass is smooth and transparent through grinding and polishing, further expansion of cracks can be blocked after heat treatment, the strength of the glass is further improved, and the service life of the glass is prolonged. The display panel is especially suitable for photoelectric display equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optoelectronic display glass, and in particular to a preparation method and application of large-size high-strength electronic glass. Background Art

[0002] With the development of architectural light and shadow, large-scale optoelectronic displays such as large-screen displays and architectural combination screen displays are increasingly attracting people's attention. The back cover of the display device is made of glass, plastic, metal and glass ceramic. There is no obvious absorption of 5G high-frequency signals. Large-size, high-strength, high-transmittance ultra-thin electronic glass can be applied to the screen and back cover of the electronic display device as protection. Due to frequent contact use, the glass used must have good bending strength and high transmittance. At present, only silicate glass can meet the use of large-size, high-strength, high-transmittance ultra-thin electronic glass. In order to solve the problems of low yield, many defects and low strength of silicate glass, it is urgent to develop a multi-component glass material to meet the preparation and process requirements of large-size, high-strength, high-transmittance ultra-thin electronic glass materials. Therefore, people are constantly committed to developing an ultra-thin electronic glass and its products with large size, high strength and high transmittance. Summary of the invention

[0003] In order to overcome the shortcomings of the background technology, the present invention provides a method for preparing large-size high-strength electronic glass and its application. The electronic glass prepared by the present invention has the characteristics of good performance, high strength, high visible light transmittance, etc., and is suitable for application in the display layer of electronic equipment.

[0004] In order to achieve the above-mentioned purpose of the invention, the present invention adopts the following technical solution: A method for preparing large-size high-strength electronic glass, the method specifically comprising the following steps: The first step is to mix the appropriate amount of raw materials and put them into the melting furnace, and control the temperature at 1500℃~1550℃ to melt and obtain uniform and stable glass liquid; The second step is to cool the glass liquid obtained in the first step to 1000-1100° C. and then pour it into the tin liquid surface in the glass forming equipment for float forming, and set a side drawing machine for thinning to obtain a base glass sheet with a thickness of 0.1-1.1 mm; Step 3: annealing the substrate glass sheet obtained in step 2 in an annealing furnace for 0.5 to 1 hour, and cooling the glass sheet to room temperature as the furnace cools; Step 4: Cut the base glass sheet obtained in the third step to obtain glass sheets of required size, use alcohol and pure water to ultrasonically clean the glass sheets in turn, dry them in an oven at 100-110° C., then grind the dried glass sheets on a grinder by vacuum adsorption, and then use a spiral micrometer to measure the thickness of the ground glass sheets, so that the average thickness is 0.2-0.3 mm. After grinding, wash and dry the ground glass sheets, and then polish the dried glass sheets on a polisher by vacuum adsorption, and use a spiral micrometer to measure the thickness, so that the average thickness is 0.19-0.29 mm. After washing and drying again, a transparent base glass sheet is obtained; Step 5: Soften the substrate glass sheet obtained in step 4, and put the softened substrate glass sheet into the annealing furnace again. The annealing time is 0.5 to 1 hour. After cooling down to room temperature in the furnace, the required qualified electronic glass is obtained.

[0005] In the method for preparing large-size high-strength electronic glass, the raw materials in the first step include the following components by mass percentage: SiO260.32~63.93%; Na2O 10.13~16.87%; CaO 5.12~9.32%; Al2O31.03~5.86%; MgO 1.95~5.02%; K2O 0~1.35%; TiO2 0~4.25%; ZrO20~2.16%; B2O3 0~2.17%.

[0006] In the method for preparing large-size high-strength electronic glass, in the first step, when the melting furnace melts the raw materials, the temperature is increased to a first set temperature at a first heating rate and then kept warm for a first set time, then the temperature is increased to a second set temperature at a second heating rate and then kept warm for a second set time, and then the temperature is increased to a third set temperature at a third heating rate and then kept warm for a third set time.

[0007] The method for preparing large-size high-strength electronic glass is as follows: the first heating rate is 12-15°C / min, the first set temperature is 1000-1200°C, and the first set time is 50-250min; the second heating rate is 12-25°C / min, the second set temperature is 1350-1400°C, and the second set time is 10-100min; the third heating rate is 5-20°C / min, the third set temperature is 1545-1550°C, and the third set time is 10-100min.

[0008] In the method for preparing large-size high-strength electronic glass, the annealing temperature of the annealing furnace in the third step is 600-650°C.

[0009] In the method for preparing large-size high-strength electronic glass, the annealing temperature of the annealing furnace in the fifth step is 500-550°C.

[0010] The large-size high-strength electronic glass is used in a photoelectric display device.

[0011] By adopting the above technical solution, the present invention has the following advantages: In the present invention, SiO2 is a network former in the structure of ultra-thin electronic glass. It forms an irregular continuous network with the structure of silicon oxygen tetrahedron [SiO4] to form a glass skeleton. Al2O3 is an intermediate oxide. When there are insufficient oxygen atoms in the glass, the coordination state of aluminum is aluminum oxygen octahedron [AlO6], which is in the network gap; when there are excess oxygen atoms in the glass, the coordination state of aluminum is aluminum oxygen tetrahedron [AlO4], which enters the ultra-thin electronic glass structure and plays a role in filling the network, increasing the stability of the ultra-thin electronic glass and increasing the strength of the ultra-thin electronic glass. Na2O and K2O are alkali metal oxides, which can reduce the glass melting temperature and improve the formability. CaO and MgO can adjust the glass forming performance, play an alkali pressure effect, and improve the stability of the ultra-thin electronic glass. TiO2 and ZrO2 can adjust the glass density. B2O3 can adjust the thermal expansion coefficient of the ultra-thin electronic glass. The ultra-thin electronic glass composed of the above components has good large-size performance, high strength, and high visible light transmittance. The base glass prepared by the present invention has high transmittance, and its surface is made smooth and transparent by grinding and polishing. After heat treatment, it can prevent further expansion of cracks and further improve the strength of the glass. It is particularly suitable for application in optoelectronic display devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a microscopic magnified picture of the glass sheet in the embodiment of the present invention. DETAILED DESCRIPTION

[0013] The present invention can be explained in more detail by the following examples, but the present invention is not limited to the following examples; In a specific implementation of the present invention, a method for preparing large-size high-strength electronic glass is provided, and the method specifically comprises the following steps: The first step is to mix the appropriate amount of raw materials and put them into the melting furnace, and control the temperature at 1500℃~1550℃ to melt and obtain uniform and stable glass liquid; During implementation, the raw materials include the following components by mass percentage: SiO260.32~63.93%; Na2O 10.13~16.87%; CaO 5.12~9.32%; Al2O31.03~5.86%; MgO 1.95~5.02%; K2O 0~1.35%; TiO2 0~4.25%; ZrO20~2.16%; B2O3 0~2.17%; Among them, SiO2 is the network former in the structure of ultra-thin electronic glass. It forms an irregular continuous network with the structure of silicon oxygen tetrahedron [SiO4] to form the glass skeleton. Al2O3 is an intermediate oxide. When there are insufficient oxygen atoms in the glass, the coordination state of aluminum is aluminum oxygen octahedron [AlO6], which is in the network gap; when there are excess oxygen atoms in the glass, the coordination state of aluminum is aluminum oxygen tetrahedron [AlO4], which enters the ultra-thin electronic glass structure and plays a role in filling the network, increasing the stability of ultra-thin electronic glass and increasing the strength of ultra-thin electronic glass. Na2O and K2O are alkali metal oxides, which can reduce the glass melting temperature and improve the formability. CaO and MgO can adjust the glass forming performance, play an alkali pressure effect, and improve the stability of ultra-thin electronic glass. TiO2 and ZrO2 can adjust the density of the glass. B2O3 can adjust the thermal expansion coefficient of ultra-thin electronic glass. The ultra-thin electronic glass composed of the above components has good large-size performance, high strength, and high visible light transmittance. Furthermore, when melting the raw materials, the smelting furnace heats the temperature to a first set temperature at a first heating rate and keeps the temperature for a first set time, then heats the temperature to a second set temperature at a second heating rate and keeps the temperature for a second set time, and then heats the temperature to a third set temperature at a third heating rate and keeps the temperature for a third set time.

[0014] In specific practice, the first heating rate is 12-15°C / min, the first set temperature is 1000-1200°C, and the first setting time is 50-250min; the second heating rate is 12-25°C / min, the second set temperature is 1350-1400°C, and the second setting time is 10-100min; the third heating rate is 5-20°C / min, the third set temperature is 1545-1550°C, and the third setting time is 10-100 min.

[0015] The second step is to cool the glass liquid obtained in the first step to 1000-1100° C. and then pour it into the tin liquid surface in the glass forming equipment for float forming, and set a side drawing machine for thinning to obtain a base glass sheet with a thickness of 0.1-1.1 mm; Step 3: annealing the substrate glass sheet obtained in step 2 in an annealing furnace for 0.5 to 1 hour, and cooling the glass sheet to room temperature as the furnace cools; During implementation, the annealing temperature of the annealing furnace is 600-650°C; Step 4: Cut the base glass sheet obtained in the third step to obtain glass sheets of required size, use alcohol and pure water to ultrasonically clean the glass sheets in turn, dry them in an oven at 100-110° C., then grind the dried glass sheets on a grinder by vacuum adsorption, and then use a spiral micrometer to measure the thickness of the ground glass sheets, so that the average thickness is 0.2-0.3 mm. After grinding, wash and dry the ground glass sheets, and then polish the dried glass sheets on a polisher by vacuum adsorption, and use a spiral micrometer to measure the thickness, so that the average thickness is 0.19-0.29 mm. After washing and drying again, a transparent base glass sheet is obtained; The fifth step is to soften the substrate glass sheet obtained in the fourth step, and put the softened substrate glass sheet into the annealing furnace again. The annealing time is 0.5 to 1 hour. During the implementation, the annealing temperature of the annealing furnace is 500 to 550°C. After cooling to room temperature with the furnace, the required qualified electronic glass is obtained.

[0016] The invention discloses a method for preparing large-size high-strength electronic glass, wherein the large-size high-strength electronic glass is applied to optoelectronic display devices.

[0017] The glass prepared by the invention has high bending strength, transparency and hardness. The surface is ground and polished and then heat treated to prevent the extension of cracks and increase the bending strength, transparency and hardness of the glass.

[0018] The glass composition selected by the present invention has a three-point bending strength of 120MPa at room temperature, a transmittance in the visible light range of more than 91%, a size of 2210*1240, and a density of less than 2.55g / cm 3 , such as Figure 1 shown.

[0019] When the present invention is implemented, high-quality batch materials are first prepared, and then the contents of aluminum oxide, magnesium oxide, calcium oxide, and sodium oxide are adjusted, and the glass network structure is adjusted. After molding and annealing, high-transmittance matrix glass is prepared and applied to the display layer of electronic equipment.

[0020] In the specific practice of the present invention, the best preparation method is as follows: The first step is to accurately weigh the weight of the raw materials, then heat the weighed raw materials to 1000°C at a rate of 10°C / min, keep warm for 10 minutes, then heat to 1200°C at a rate of 5°C / min, keep warm for 20 minutes, then heat to 1550°C at a rate of 5°C / min, keep warm for 100 minutes, and obtain glass liquid; Step 2: Cool the glass liquid to 1100℃, pour it onto the surface of the tin liquid, and stretch it into thin shape; Step 3: Place the substrate glass sheet obtained in the previous step into an annealing furnace heated to 600° C. and cool it down to room temperature; Step 4: After cutting, a 0.33 mm thick thin glass sheet is obtained. The 0.33 mm glass sheet is ultrasonically cleaned with alcohol and pure water in turn, dried in an oven at 105° C., then ground on a grinder using vacuum adsorption, and its thickness is measured with a spiral micrometer to make its average thickness 0.26 mm. After cleaning and drying, it is polished on a polishing machine using vacuum adsorption, and its thickness is measured with a spiral micrometer to make its average thickness 0.25 mm. After cleaning and drying, a transparent substrate glass sheet is obtained; Step 5: According to the expansion softening point and glass transition temperature of the base glass, a suitable softening process is set, and the base glass sheet is placed in an annealing furnace and heat treated according to the process to obtain high-strength and high-hardness electronic glass; The density of the matrix glass measured by a density meter is 2.412 g / cm 3 The transmittance of the substrate glass under visible light wavelength was measured by a haze meter, and the average transmittance of the substrate glass under visible light wavelength was 91.2%, the three-point bending strength was 120MPa, and the Vickers hardness value of the substrate glass was 451kgf / mm by a Vickers hardness tester. 2 .

[0021] Parts of the present invention not described in detail are prior art.

[0022] The embodiments selected herein for the purpose of disclosing the invention are currently considered to be suitable, but it should be understood that the invention is intended to include all changes and modifications of the embodiments that fall within the scope of the concept and invention.

Claims

1. A method for preparing large-size high-strength electronic glass, characterized in that: The method specifically comprises the following steps: The first step is to mix the appropriate amount of raw materials and put them into the melting furnace, and control the temperature at 1500℃~1550℃ to melt and obtain uniform and stable glass liquid; The second step is to cool the glass liquid obtained in the first step to 1000-1100° C. and then pour it into the tin liquid surface in the glass forming equipment for float forming, and set a side drawing machine for thinning to obtain a base glass sheet with a thickness of 0.1-1.1 mm; Step 3: annealing the substrate glass sheet obtained in step 2 in an annealing furnace for 0.5 to 1 hour, and cooling the glass sheet to room temperature as the furnace cools; Step 4: Cut the base glass sheet obtained in the third step to obtain glass sheets of required size, use alcohol and pure water to ultrasonically clean the glass sheets in turn, dry them in an oven at 100-110° C., then grind the dried glass sheets on a grinder by vacuum adsorption, and then use a spiral micrometer to measure the thickness of the ground glass sheets, so that the average thickness is 0.2-0.3 mm. After grinding, wash and dry the ground glass sheets, and then polish the dried glass sheets on a polisher by vacuum adsorption, and use a spiral micrometer to measure the thickness, so that the average thickness is 0.19-0.29 mm. After washing and drying again, a transparent base glass sheet is obtained; Step 5: Soften the substrate glass sheet obtained in step 4, and put the softened substrate glass sheet into the annealing furnace again. The annealing time is 0.5 to 1 hour. After cooling down to room temperature in the furnace, the required qualified electronic glass is obtained.

2. The method for preparing large-size high-strength electronic glass according to claim 1, characterized in that: The raw materials in the first step include the following components by mass percentage: SiO260.32~63.93%; Na2O 10.13~16.87%; CaO 5.12~9.32%; Al2O31.03~5.86%; MgO 1.95~5.02%; K2O 0~1.35%; TiO2 0~4.25%; ZrO20~2.16%; B2O3 0~2.17%.

3. The method for preparing large-size high-strength electronic glass according to claim 1, characterized in that: In the first step, when the smelting furnace melts the raw materials, the temperature is increased to the first set temperature at a first heating rate and then kept at the first set time, then the temperature is increased to the second set temperature at a second heating rate and then kept at the second set time, and then the temperature is increased to the third set temperature at a third heating rate and then kept at the third set time.

4. The method for preparing large-size high-strength electronic glass according to claim 3, characterized in that: The first heating rate is 12-15°C / min, the first set temperature is 1000-1200°C, and the first set time is 50-250min. The second heating rate is 12-25°C / min, the second set temperature is 1350-1400°C, and the second set time is 10-100min. The third heating rate is 5-20°C / min, the third set temperature is 1545-1550°C, and the third set time is 10-100 min.

5. The method for preparing large-size high-strength electronic glass according to claim 1, characterized in that: The annealing temperature of the annealing furnace in the third step is 600-650°C.

6. The method for preparing large-size high-strength electronic glass according to claim 1, characterized in that: The annealing temperature of the annealing furnace in the fifth step is 500-550°C.

7. The method for preparing large-size high-strength electronic glass according to claim 1, characterized in that: The large-size high-strength electronic glass is applied to optoelectronic display devices.

Citation Information

Cited By

  • Preparation method and application of high-flatness electronic glass

    CN121651646A